Engagement/involvement of staff from public medical Institutions with pregnant women experiencing intimate partner violence - a systematic review of African & South African literature - Adams, Faseegah (Department of Social Development, 2025)
This study explores how staff at public health care institutions respond to intimate partner violence (IPV) experienced by pregnant women living in South Africa and Africa. This study aimed to investigate what protocols/pathways staff at public health care institutions (PHCI) use to identify, screen, report, record and refer instances of IPV. The motivation for this study was to bring awareness of IPV during pregnancy. Since learning the high statistics of IPV during pregnancy, the researcher was prompted to investigate what PHCI are doing to identify, screen, report, record and refer cases of IPV. In addition, the researcher hopes that this research can facilitate policy development for staff at PHCI on how best to respond to pregnant women experiencing IPV. The methodology used in this study was a systematic literature review, that reviewed 14 qualitative journal articles. PICo was used to identify the study participants, the Cochrane systematic review methodology was used and the PRISMA flow diagram. Using thematic analysis, the researcher used Dey and Tesch to analyse the data. The findings indicate that there are no pathways/protocols for identifying, screening, reporting recording and refereeing instances of IPV in South Africa or Africa. There were also no direct policies or frameworks established at PHCI to manage intimate violence during pregnancy. The research identifies some of the main barriers/challenges to IPV enquiry which are lack of privacy at public health care institutions, training and awareness of IPV during pregnancy, staff agency, staff safety and cultural beliefs. These results contribute to the research regarding how PHCI in South Africa and Africa respond to IPV. Thus shifting focus away from the criminal justice system and more toward PHCI as IPV during pregnancy has grave health implications. This study provides new insights on how to build and improve protocol/pathways at PHCI. This study highlights the daily challenges that staff at PHCI face when enquiring about IPV. It concludes by discussing how The National Council on Gender-Based Violence Femicide can use information on the challenges/barriers to enquiry to achieve the goals and aims set out in The National Strategy Plan addressing gender-based violence and femicide in South Africa and Africa.